Intrauterine cannabis exposure and fetal and maternal blood flow: a case–control study. (30th August 2022) - Brik, Maia; Sandonis, Miguel; Gil, Judit; Hernandez‐Fleury, Alina; Parramón‐Puig, Gemma; Maiz, Nerea; Suy, Anna; Carreras, Elena
Abstract: Introduction: Cannabis consumption during pregnancy increases the risk of pregnancy and neonatal complications. Since the underlying mechanism is unknown, the purpose of this study is to evaluate the changes in maternal and fetal blood flow in pregnancies exposed to cannabis, Δ9‐tetrahydrocannabinol (THC). Material and methods: A case–control study between 2013 and 2020, included women with continued cannabis exposure during the pregnancies, defined by qualitative detection of THC in urine (Cannabis Group), and low‐risk pregnancy women divided into tobacco smokers (Tobacco Group), and non‐tobacco smokers (Control Group). We evaluated the association between cannabis consumption and maternal and fetal blood flow parameters measured by Doppler ultrasound: uterine artery at 11–14, 20–22 and 33–35 weeks, umbilical artery and middle cerebral artery at 33–35 weeks. Cerebral‐placental ratio was calculated. Results: Overall, 275 participants were included, 60 in the Cannabis Group, 17 in the Tobacco Group and 198 in the Control Group. At 33–35 weeks, differences were found in the umbilical artery pulsatility index (PI) (1.05 ± 0.23, 1.06 ± 0.19, 0.93 ± 0.15, P < 0.01), middle cerebral artery PI (1.75 ± 0.35, 1.90 ± 0.45, 1.88 ± 0.34, P < 0.05), cerebral‐placental ratio (1.69 ± 0.40, 1.85 ± 0.53, 2.07 ± 0.47, P < 0.05) and mean uterine artery PI (0.89 ± 0.26, 0.73 ± 0.19, 0.74 ± 0.20, P < 0.01), respectively. On logistic regression analysis, adjusted for maternal age, maternal body mass index, maternal weight and white ethnicity, both cannabis and tobacco were predictors for increased umbilical artery PI, but only cannabis was a predictor for a decreased cerebral‐placental ratio and an increased uterine artery PI at 33–35 weeks. Conclusions: Data from a large cohort of continuous cannabis exposure pregnancies show that cannabis is associated with maternal and fetal blood flow changes. However, it is not possible to disentangle the association of the tobacco and cannabis. Abstract : Continuous cannabis exposure pregnancies showed that cannabis is associated with maternal and fetal blood flow changes. Nevertheless, it is not possible to disentangle the association of the tobacco and cannabis